2004
DOI: 10.1007/s00056-004-0327-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Loading Rate on Bond Strength

Abstract: The purpose of this study was to examine the effect of loading rate on the bond strength of brackets bonded to enamel. Forty premolars were used and brackets were bonded with a chemically cured or a light-cured adhesive, mounted on a testing machine, and debonded under shear stress at two loading velocities: a standard 1 mm/min, and a fast 200 mm/min which better approximates the actual jaw velocity during chewing. Bond strength results (N) were analyzed with two-way analysis of variance (loading rate, adhesiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
1
10
0
4
Order By: Relevance
“…In this study, a crosshead speed of 1 mm/min was selected, although previous studies have reported speeds ranging from 0.5 to 5 mm/min. 11 In any case, these ranges of crosshead speeds lack relevance to clinical conditions, 12,13 in which even 200 mm/min is considered to be lower than the intraoral condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a crosshead speed of 1 mm/min was selected, although previous studies have reported speeds ranging from 0.5 to 5 mm/min. 11 In any case, these ranges of crosshead speeds lack relevance to clinical conditions, 12,13 in which even 200 mm/min is considered to be lower than the intraoral condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported in relevant literature 14,15 that the minimum adequate bond strength should be between 6 and 8 MPa. However, this ''threshold strength'' approach has been criticized in that it overlooks the intraoral degradation of adhesive resin 12,13 caused by fatigue, 16 temperature and pH variations, 17 and microbial degradation. 18 Additionally, previous studies 19,20 have shown that in vivo-aged bond strengths are significantly lower than the strength of artificially aged laboratory-tested bonds.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to the findings of Finemma et al, 9 and no clear physicochemical explanation was found for the High discrepancies with other studies. 35,36 The increase of 0.5 mm/min seems to be low to be related to the elimination of the viscoelastic response of the polymeric adhesive and a consequent induction of a stiff body response. 37 One suggestion is that, with 0.5 mm/ min speed, the chisel would be in contact with the body for a longer time, increasing the strains in the bond interface, whereas the contact period of the 1.0 mm/ min speed would be shorter, decreasing strain and thus increasing bond strength.…”
Section: Discussionmentioning
confidence: 95%
“…Nos grupos avaliados, os valores das médias de resistência de união indicam que o uso do monômero de metilmetacrilato associado ou não ao cianoacrilato podem ser utilizados clinicamente para adesão de bráquetes metálicos à superfície de resina acrílica, visando a permanência do acessório durante o tratamento ortodôntico, minimizando o descolamento. No entanto, é importante considerar que existe uma influência da degradação intraoral da resistência adesiva [34,35] causada por fadiga [36], temperatura, variações de pH [37] e degradação microbiológica [38]. Além disso, resina acrílica ou composta mantém uma força de ligação acima do nível aceitável para utilização clínica [10,11].…”
Section: Discussionunclassified